China-Africa co-operation in structural transformation: Ideas, opportunities, and finances - Justin Yifu Lin; Yan Wang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines China and Africa co-operation from the angle of structural transformation as a major driver of growth and job creation. Being a bit ahead in the structural transformation process, China can provide ideas, tacit knowledge, opportunities as well as development finances in Africa's transformation. We review critical parts of China's transformation to see if these ideas are relevant for Africa. We use empirical evidence from China-Africa co-operation and find that China-financed infrastructure projects do address Africa's infrastructure bottlenecks and hence contribute to structural transformation. In addition, China's industrial upgrading and outward investments provide opportunities for light manufacturing development in low-income developing countries. Building cluster-based industrial zones has the potential to seize the opportunities for job creation in the labour-intensive light-manufacturing sectors. Further, expanding the definition of international aid could induce more development financing from various sources.
Keywords: L5; O1; O4; E2; 330; structural transformation; development co-operation; development finance; China; Africa